Discovery of New Catalytic Topoisomerase II Inhibitors for Anticancer Therapeutics - Matias-Barrios, Victor M.; Radaeva, Mariia; Song, Yi; Alperstein, Zaccary; Lee, Ahn R.; Schmitt, Veronika; Lee, Joseph; Ban, Fuqiang; Xie, Ning; Qi, Jianfei; Lallous, Nada; Gleave, Martin E.; et al. (Frontiers in Oncology, 2021)
Poison inhibitors of DNA topoisomerase II (TOP2) are clinically used drugs that cause cancer cell death by inducing DNA damage, which mechanism of action is also associated with serious side effects such as secondary malignancy and cardiotoxicity. In contrast, TOP2 catalytic inhibitors induce limited DNA damage, have low cytotoxicity, and are effective in suppressing cancer cell proliferation. They have been sought after to be prospective anticancer therapies. Herein the discovery of new TOP2 catalytic inhibitors is described. A new druggable pocket of TOP2 protein at its DNA binding domain was used as a docking site to virtually screen ~6 million molecules from the ZINC15 library. The lead compound, T60, was characterized to be a catalytic TOP2 inhibitor that binds TOP2 protein and disrupts TOP2 from interacting with DNA, resulting in no DNA cleavage. It has low cytotoxicity, but strongly inhibits cancer cell proliferation and xenograft growth. T60 also inhibits androgen receptor activity and prostate cancer cell growth. These results indicate that T60 is a promising candidate compound that can be further developed into new anticancer drugs.